A Review on Dalk (Massage) with Special Reference to the Prescribed Mediciations - Sadia Nikhat; Mohd Fazil (Tehran University of Medical Sciences, 2017)
Dalk is one of the oldest forms of therapies in use since ancient times. It involves the manipulation of body tissues with hands, cloth or any suitable object. In Unani medicine, dalk is based on the principle of tanqiyah (expulsion) and imāla (diversion). In addition to the comforting feeling provided by human touch, massage has been demonstrated to have clinically significant physiological effects on the body. It increases blood flow, reduces stress and also has immediate sedative effects. Depending on the individual patient, different types of dalk are described which are used in combination with certain medicines or oils, or with bare hands for different disorders. Although largely a safe therapy, a few contraindications do exist, which are mainly advised for prevention of any adverse events. Unani physicians made significant advances into dalk and devised specific prescriptions for a large number of ailments. The prescribed formulations for dalk are mostly oils, but in certain conditions the decoction, paste, powder or extract of drugs is also prescribed, the basis of which is the individual mizāj (temperament) and also the disease.